Synthesis, characterization, and investigation of nitric oxide donors for bacterial detection and antibacterial activity - Hibbard, Hailey Althea Jane, author; Reynolds, Melissa M., advisor; Crans, Debbie, committee member; Bailey, Travis, committee member; Popat, Ketul, committee member (Colorado State University. Libraries, 2020)
Antibiotic resistance is a critical problem, especially with the emergence of "superbugs," which are bacteria species that have become immune to most common antibiotics. To address this alarming issue, it is necessary to both prevent the overuse of current antimicrobial therapeutics, and to develop new, effective antibacterial treatments. By detecting when the source of a patient's infection is bacterial, and which species is causing the infection, antibiotics can be prescribed only when they are needed, and the most effective antibiotic can be chosen. The development of new antibiotics with new mechanisms of action are also a productive path to help solve the problem of antibiotic resistance. Bacteria that encounter antibiotics with novel mechanisms of action have not yet evolved pathways to resistance against the therapeutic, so these innovative compounds will be highly successful at eradicating infections. Nitric oxide is a small molecule with potent antibacterial activity due to its reactivity and ability to form reactive nitrogen species, which induces nitrosative stress in bacteria cells and cell death. The development of a new antibiotic incorporating nitric oxide could lead to a very powerful antibacterial agent. Combining the ideas of detecting bacterial infections with the antibiotic potential of nitric oxide into a multifunctional molecule would give the benefits of both detection of a bacterial infection, and potent antimicrobial action. The focus of this work is to develop a small molecule to both sense and kill bacteria. This goal is accomplished through the development of a dual-function small molecule to detect and kill bacteria through a colorimetric change and release of nitric oxide to kill bacteria. Another approach to achieve this goal is the synthesis of a molecule that bacteria can sense, an inactive drug until bacterial enzymes cause the release of nitric oxide to kill the bacteria. Nitric oxide release is localized to bacteria causing an infection, which can help prevent bacteria from developing resistance by avoiding unnecessary exposure. Toward the goal of addressing the problem of antibiotic resistance, a nitric oxide donor attached to a fluorescent compound is synthesized, creating a compound that can both detect and kill the deadly multi-drug resistant bacteria strain, Pseudomonas aeruginosa. Detection occurs through a bacterial enzyme-activated color change, showing a visible color change from blue to yellow under UV light. The synthesized compound spontaneously releases 853 µmol of nitric oxide/g at a 10 mM initial concentration of the compound. Antibacterial efficacy studies after exposing Pseudomonas aeruginosa to a 10 mM dose of the synthesized compound show a 65% reduction in bacteria after 24 hours. This work is the first instance of a small molecule dual-function material that can both detect and kill bacteria. To address the goal of developing a bacteria-specific nitric oxide releasing compound, novel nitroaromatic-protected piperazine diazeniumdiolate (nitric oxide donor) prodrugs are synthesized to release nitric oxide upon enzyme activation to kill bacteria. These prodrugs are activated by an enzyme in the nitroreductase family, which are found almost exclusively in bacteria, and reduces the nitroaromatic-protecting group of the synthesized compounds, catalyzing the release of nitric oxide. Experiments show that nitric oxide release from the synthesized compounds only occurs in the presence of a bacteria-derived nitroreductase enzyme, demonstrating the possibility of site-specific delivery of an antibacterial therapeutic. The amount of nitric oxide release is measured at concentrations of 0.01, 0.1, and 1 mM, and is well within known antibacterial levels at concentrations of 0.1 and 1 mM, reaching nitric oxide concentrations of up to 4.8 µM. The antibacterial activity of the compounds is demonstrated after exposure of the compounds to Escherichia coli, a nitroreductase-producing bacterial species and common infection forming species, leading to up to a 94% reduction in the number of viable bacteria after 24 hours at 1 mM concentrations of the prodrug. This study is the first example of an antibacterial diazeniumdiolate prodrug activated by a nitroreductase enzyme, and further demonstrates the possibilities of antibacterial prodrugs. Medical devices are a site where bacterial infections can develop, and these infections are often incredibly difficult to treat, sometimes requiring the removal of the device. Medical devices could be coated with an antibacterial material that releases antibiotics to prevent infections. To investigate the application of the nitroreductase enzyme-activated nitric oxide releasing prodrugs for antibacterial medical device coatings, the prodrugs are incorporated into polyvinyl chloride and polyurethane films to create antibacterial prodrug polymer composite materials. Characterization of nitric oxide release from the surface of the composite films is observed only after metabolism by a bacterial nitroreductase enzyme, demonstrating the prodrug nature of the polymer composite. Excitingly, antibacterial efficacy experiments resulted in a 66% reduction in Escherichia coli after exposure to the diazeniumdiolate-composite films. This work details the first example of an antibacterial enzyme-activated NO-releasing polymer. The development of these novel compounds and materials represents significant advances in research to develop new ways to detect and treat bacterial infections.
Keywords: diazeniumdiolates; antibacterial; nitric oxide